Santo Domingo and after: the challenges for the Latin American Church - Gutiérrez, Gustavo (Catholic Institute for International Relations, 1993)
The Santo Domingo conference / Francis McDonagh -- The winds of Santo Domingo and the evangelisation of culture / Jon Sobrino -- An agenda / Gustavo Gutiérrez -- Reflections on collegiality : a letter to my brother bishops / Cándido Padin